INTEGRASI MODEL PEMBELAJARAN BERBASIS MASALAH DENGAN LEMBAR KERJA INKUIRI TERBIMBING UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS DAN KEMAMPUAN BERPIKIR KRITIS - Khairil Anbiya; Muhibbudin; Ibnu Khaldun; Yusrizal (Postgraduate, University of Mataram, 2023)
The low ability of students to comprehend and connect information, as well as the problems they face, contributes to a low level of scientific literacy. The application of the integration of problem-based learning models with guided inquiry worksheets in this study aims to examine the improvement of students' scientific process skills (SPS) and critical thinking abilities (CTA). A non-equivalent control group design with pretest-posttest was used as the research design. The sample consisted of students from Class X MIA-1 and X MIA-2, selected through purposive sampling technique. Data obtained from the observation sheets on SPS and test questions were analyzed using the SPSS application with the analysis of covariance (ANCOVA) test. The results showed a probability sig. of 0.907 > 0.05 for SPS and a probability sig. of 0.598 < 0.05 for CTA. The research findings concluded that the application of the integration of problem-based learning models with guided inquiry worksheets can significantly enhance students' scientific process skills and critical thinking abilities.